Fetus in fetu - the included twin/entrapped twin: a case report - Khaladkar, Sanjay M.; Koganti, Venkata Sai Mani Deepak; Jadhav, Vikas Leelavati Balasaheb; Khandelwal, Rachit; Lamghare, Purnachandra (Paediatrica Indonesiana, 2023)
Fetus in fetu is a rare congenital anomaly with fewer than 200 cases reported worldwide. It is a part of spectrum of anomalous embryogenesis. We report a case of an 18-month old boy with abdominal distension. Ultrasonography, X-ray, and computed tomography (CT) scan revealed a retroperitoneal mass suggestive of fetus in fetu. with evidence of organogenesis and a vertebral column, which differentiates it from an organized teratoma. The mass was resected in toto.